2023
DOI: 10.1186/s13028-023-00688-9
|View full text |Cite
|
Sign up to set email alerts
|

A survey for antibodies against Fasciola hepatica in cattle and sheep in Finland indicates a low level of exposure

Heini Gröning,
Antti Oksanen,
Teresa Skrzypczak
et al.

Abstract: Background Fasciolosis is a parasitic infection caused by the liver fluke Fasciola hepatica that can have a major economic impact on livestock industry. The prevalence of the disease has recently been increasing in many North European countries. The objective of this study was to determine the prevalence of antibody against F. hepatica in Finnish cattle herds and sheep flocks during 2019 by using a commercial enzyme-linked immunosorbent assay (ELISA). Randomly selected bulk tank milk samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
0
1
Order By: Relevance
“…In addition, in freshwater snails, we found that some of the cercariae tail had already broken off inside the snail and formed fresh, milky-white “gourd-type” metacercariaes. This is different from the cercariae that overflowed out of the snail and developed into metacercari in the water as reported by Groning et al (2023) .…”
Section: Discusscontrasting
confidence: 84%
“…In addition, in freshwater snails, we found that some of the cercariae tail had already broken off inside the snail and formed fresh, milky-white “gourd-type” metacercariaes. This is different from the cercariae that overflowed out of the snail and developed into metacercari in the water as reported by Groning et al (2023) .…”
Section: Discusscontrasting
confidence: 84%